Analisis Elastisitas Dan Tax Effort Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) terhadap Produk Domestik Regional Bruto (PDRB) di Kota Banjarbaru Tahun 2011-2020 - Ichsanul Arief; Saipudin Saipudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research aims to (1) Determine the level of elasticity of changes in GRDP caused by changes in BPHTB revenue in Banjarbaru for the 2011-2020 period and (2) To determine the tax efforts of BPHTB in the City of Banjarbaru for the period 2011-2020. This research uses descriptive quantitative research methods.This research uses descriptive quantitative research methods. The data used is secondary data sourced from the Central Bureau of Statistics and the Regional Tax and Retribution Management Agencies of Banjarbaru in 2011-2020. The results of the study show that from 2011-2020 as follows: (1) the elasticity level of GRDP changes caused by changes in Banjarbaru City BPHTB revenue has an average of 0.38% which means it tends to be inelastic or a value of less than 1 (E<1) . This indicates that BPHTB will experience a change of 1% due to an increase or decrease of less than 1% by GRDP. So that the growth of BPHTB revenue does not cause significant and significant changes (inelastic) due to changes in GRDP. (2) The level of tax effort also has an average value below 1, namely 0.404 (close to 0). The ability of the local government of Banjarbaru to collect BPHTB taxes is still low because it is far from the perfect value of tax effort, which is 1.